Policy on the Implementation of Smoke-Free Areas in the Technical Implementation Unit of West Kalimantan Provincial Health Laboratory - Dwisulasti, Elisabet (JPASDEV : Journal of Public Administration and Sociology of Development, 2025)
This study aims to determine and analyze the implementation of the Non-Smoking Area (KTR) policy, and the factors of whether or not KTR is complied with by the apparatus in the West Kalimantan Provincial Health Laboratory Technical Implementation Unit . This study used a qualitative approach in which the data were analyzed descriptively. This research was conducted at the West Kalimantan Province Health Laboratory Technical Implementation Unit , while the parties who were used as informants included: Head of the West Kalimantan Province Health Laboratory Technical Implementation Unit, and apparatus or staff at the West Kalimantan Provincial Health Laboratory Technical Implementation Unit as well as those that don't smoke nor those who have habit smoke the patient was determined purposively. The results showed that there were still officers who smoked in the KTR and in places provided for smoking every day. The weak supervision of KTR implementers has made the environment in the West Kalimantan Provincial Health Laboratory Technical Implementation Unit not yet free from exposure to cigarette smoke. Moreover, the sanctions given were limited to warnings and formalities in nature. As for the factors that cause non-compliance with the KTR because there are still elements of the leadership who still have smoking habits. The lack of coordination between policy implementers and officials who have smoking habits, makes smoking awareness still requires seriousness in implementing KTR which is not just a follow-up to other activities/programs in the West Kalimantan Provincial Health Laboratory Technical Implementation Unit . On the other hand, the KTR policy is complied with because the KTR is a national program that must be supported and its implementation must be reflected. Moreover, the West Kalimantan Provincial Health Laboratory Technical Implementation Unit is an element of government agencies that must support and implement as appropriate.